The umbilical cutaneous "Y-to-V" plastic surgery in the care of pedunculated umbilical hernia in the infant and the child - Aloïse Sagna; Aïssata Ly; Ibrahima Fall (Elsevier, 2014)
Pedunculated umbilical hernia in the African infant and child raise an important cosmetic problem by the skin excess they present. Several solutions are proposed from simple reduction to complete cutaneous excision followed by skin grafting. In this paper we report our experience of umbilical cutaneous "Y-to-V" plasty in surgical hernia repair in the infant and the child in Senegal. A two years prospective study includes hernia with diameters included in 2-5 cm and a height or cutaneous projection of at least 1.5 cm. The surgical procedure starts with pencil drawings; follows a primary incision of the vertical branch of the "Y" and a circular subcutaneous undermining. Then, herniorrhaphy is performed and umbilical skin excess resected according to lateral twin isosceles triangles flaps making the "V". Finally we perform subcutaneous quilting stitches of the umbilical residual flap and intradermal running suture of the wound. Aesthetic variables such as scar quality, shape and depth of the new umbilical valley, aspects of peripheral landscape, are itemized and analyzed. The cohort was made up of 80 children; 50 females and 30 males, among which 60 infants aged between one to six months. The age average is 5 months with extremes of 1 month and 7 years. The operations were performed by the same surgeon. The post-operative follow up has had no repercussions, except in five cases where we have noticed superficial suppuration. The recorded results using evaluation criteria are good in 70 cases (New umbilical valley well-drawn, peripheral landscape with clear outlines, scar hidden away), satisfactory in 7 cases (New umbilical valley little-drawn, prominent peripheral landscape, visible scar) and bad in 3 cases (Nonexistent umbilical valley, hypertrophic peripheral landscape, unsightly scar). The authors of this paper highlight the need for aesthetic surgery together with parietal defect repair and give precise different umbilical cosmetic criteria.